Reliability and Validity of the Turkish Version of Work-Related Questionnaire for Upper Extremity Disorders (WORQ-UP) - Koç, Meltem; Dal, Cansu; Bulut, Emin Kürşat; Bayar, Banu; Bayar, Kılıçhan (La Medicina del Lavoro, 2024)
Background: The Work-Related Questionnaire for Upper Extremity Disorders (WORQ-UP) serves as a patient-reported outcome measure to identify work-related limitations in individuals with upper extremity musculoskeletal disorders. This study aims to adapt the WORQ-UP into Turkish and subsequently evaluate its validity and reliability. Methods: The Turkish WORQ-UP, along with the previously validated Turkish Quick DASH, were administered to 136 patients. The Turkish WORQ-UP was applied twice within a 7-14 day interval to assess test-retest reliability. Reliability was assessed using measures of internal consistency and intraclass correlation coefficient (ICC). For validity assessment, Spearman correlation coefficients were calculated between the Turkish WORQ-UP and Quick DASH, and Explanatory (EFA) and Confirmatory factor analysis (CFA) were conducted. Results:  In the reliability analysis, items 11, 12, 13, 15, and 16, which did not meet the criterion of item total score correlation >30, were excluded, resulting in a 12-item Turkish WORQ-UP with satisfactory validity and reliability outcomes. The Cronbach's alpha and ICC were calculated as 0.895 and 0.879, respectively, while the SEM and MDC were determined to be 0.93 and 1.85. In the EFA, the Kaiser-Meyer-Olkin measure (0.895) and Bartlett's tests were both significant (p < 0.001). Additionally, the CFA indicated an acceptable fit with two factors. The goodness of fit indices, including χ2/df = 2.09, CFI = 0.934, TLI = 0.918, and RMSEA = 0.08, confirmed the adequacy of the model. The 12-item Turkish WORQ-UP showed a significant and strong correlation (r = 0.754; p < 0.001) with Quick DASH. Conclusion: The Turkish version of WORQ-UP with 12 items had proper psychometric properties to identify work-related limitations in individuals with upper extremity musculoskeletal disorders.